PENGARUH BIAYA PRODUKSI DAN BIAYA OPERASIONAL TERHADAP PENJUALAN PADA PERUSAHAAN MANUFAKTUR SUB INDUSTRI TEKSTIL DAN GARMEN YANG TERDAFTAR DI BURSA EFEK INDONESIA - khairaningrum Mulyanti; Fransiscus Naibaho (LAND JOURNAL, 2026)
The textile and garment industry contributes significantly to Indonesia’s economy through employment absorption and export performance. Nevertheless, manufacturing companies in this subsector listed on the Indonesia Stock Exchange face major challenges regarding the efficiency of production and operational costs. This study investigates the effect of production costs and operating costs on sales. A quantitative method with a causal design was applied. Secondary data were obtained from annual financial reports for the period 2021–2024 accessed via the Indonesia Stock Exchange. Analytical techniques employed include multiple regression, t-tests, f-tests, product moment correlation, multiple correlation, coefficient of determination, and classical assumption tests. The findings indicate that both production costs and operating cost individually have a positive effect on sales, while jointly they exert a significant influence on sales. These results highlight the importance of cost efficiency in production and operations as a strategic factor to enhance competitiveness and sustain corporate profitability in a dynamic market environment.